PERANCANGAN SISTEM INFORMASI PENJUALAN TIKET KAPAL BERBASIS WEB STUDI KASUS SB RAHMAT JAYA - Sitinjak, Judika Bestian; Andema, Henky (Program Studi Sistem Informasi Institut Indobaru Nasional, 2024)
Currently the use of internet services as a means to obtain information is increasingly being used. Because of its wide reach, the internet is ideal when used as a means of promotion and means of publishing information. The purpose of making this web program is to promote the company while providing services to customers regarding on-line ticket bookings. The internet is a very potential medium for developing a dynamic and wide-scale information system, with the internet information about anything can be obtained easily and quickly. Based on the various conveniences and uses that the internet has, a